2011
DOI: 10.1007/s00404-011-1978-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to study the effect of IV hydration on the duration of labor in nulliparous women

Abstract: This study establishes a trend towards decreased incidence of prolonged labor and less vomiting in patients receiving intravenous hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
0
18
1
Order By: Relevance
“…These findings are in accordance with, GARITE, et al, 2000 [17] who found that, inadequate hydration in labor may be a factor contributing to dysfunctional labor and possibly cesarean delivery. This result disagrees with that of Kavitha, (2012) [14] who reported that, there was no statistically significant reduction in the number of caesarean sections (CS) in the intravenous fluid group (risk ratio (RR) 0.73, 95% CI 0.49 to 1.08,) in the two studies (315 women). On the other hand, there was no statistically significant difference between both groups regarding perineal lacerations, and maternal complications.…”
Section: Discussioncontrasting
confidence: 75%
“…These findings are in accordance with, GARITE, et al, 2000 [17] who found that, inadequate hydration in labor may be a factor contributing to dysfunctional labor and possibly cesarean delivery. This result disagrees with that of Kavitha, (2012) [14] who reported that, there was no statistically significant reduction in the number of caesarean sections (CS) in the intravenous fluid group (risk ratio (RR) 0.73, 95% CI 0.49 to 1.08,) in the two studies (315 women). On the other hand, there was no statistically significant difference between both groups regarding perineal lacerations, and maternal complications.…”
Section: Discussioncontrasting
confidence: 75%
“…Multiple randomized controlled trials (RCTs) have compared intravenous fluid rates of 125-250 mL/h in laboring nulliparous women (7)(8)(9)(10)(11)(12)(13)(14). Many of these studies have demonstrated clinically significant reductions in the rate of cesarean delivery but others have not.…”
Section: Introductionmentioning
confidence: 99%
“…Several smaller studies have not consistently confirmed these findings. 10,11,12 IV infusion rates were not specifically controlled in our protocol, but the overall infusion amounts did not differ between groups. The lower amount of study fluids in the D5LR group is explained by the use of LR for all IV fluid boluses regardless of group.…”
Section: Discussionmentioning
confidence: 99%